Outsourcing at Office Supply Inc - Jeffery, Mark; Anfield, James; Bhowmick, Subhankar ([London] : SAGE, 2016)
This case is designed to teach how to structure information technology (IT) infrastructure outsourcing deals from both the outsourcer and the client perspective. Office Supply Incorporated (OSI) is a company in crisis, with challenges in its cost structure and poor IT performance. Outsourcing to Technology Infrastructure Solutions is an opportunity to both reduce costs and complexity for the firm, but students first must consider whether outsourcing is a good strategic fit for OSI. Detailed spreadsheet templates are given that are based on a real outsourcing client engagement for a major infrastructure outsourcing company. The spreadsheets are complex but have been simplified so that they automatically calculate when populated, allowing the students to quickly move to answering the management challenge: how should TIS price and structure.
Originally Published in: Jeffery, M., Anfield, J., & Bhowmick, S. (2009). Outsourcing at Office Supply, Inc. 5-107-013. Evanston, IL: Kellogg School of Management, Northwestern University.
Description based on online resource; title from home page (viewed on April 27, 2016).
Keywords: elektronické knihy; electronic books; Information technology -- Contracting out -- Case studies; Contracting out -- Case studies